Paravertebral block for radiologically inserted gastrostomy tube placement in amyotrophic lateral sclerosis. Issue 1 (28th April 2020) - Porter, Steven B.; McClain, Robert L.; Robards, Christopher B.; Paz‐Fumagalli, Ricardo; Clendenen, Steven R.; Logvinov, Ilana I.; Hex, Karina O.; Palmucci, Carla; Oskarsson, Björn E.
Abstract: Introduction: Radiologically inserted gastrostomy (RIG) placement in patients with amyotrophic lateral sclerosis (ALS) carries risks related to periprocedural sedation and analgesia. To minimize these risks, we used a paravertebral block (PVB) technique for RIG placement. Methods: We retrospectively reviewed patients with ALS undergoing RIG placement under PVB between 2013 and 2017. Results: Ninety‐nine patients with ALS underwent RIG placement under PVB. Median (range) age was 66 (28 to 86) years, ALS Functional Rating Scale—Revised score was 27 (6 to 45), and forced vital capacity was 47% (8%–79%) at time of RIG placement. Eighty‐five (85.9%) patients underwent RIG placement as outpatients, with a mean postanesthesia care unit stay of 2.3 hours. The readmission rate was 4% at both 1 and 30 days postprocedure. Discussion: PVB for RIG placement has a low rate of adverse events and provides effective periprocedural analgesia in patients with ALS, the majority of whom can be treated as outpatients. Abstract : See editorial on pages 5–6 in this xsissue .